2019
DOI: 10.1111/jpc.14677
|View full text |Cite
|
Sign up to set email alerts
|

Injuries due to foreign body ingestion and insertion in children: 10 years of experience at a single institution

Abstract: Aim: Foreign body (FB) injuries represent a severe public health problem during childhood. The aim of this study was to report our experience with patients with injuries due to FB ingestion and insertion who were treated surgically at our institution. Methods: A total of 78 paediatric patients who were hospitalised for FB injuries were retrospectively reviewed. Results: The series was composed of 27 males and 51 females, with a median age of 3.6 years. The cases included 35 cases of FB ingestion and 43 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
3
4
2
Order By: Relevance
“…The majority of ingested FBs passed spontaneously through the gastrointestinal tract without causing injury. However, some can cause serious complications which might require surgical intervention [4]. In our study, Abdominal pain, vomiting and paroxysmal crying were the common symptoms in the rst group which similar to other pediatric digestive diseases like appendicitis, intussusception and mesenteric lymphadenitis.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The majority of ingested FBs passed spontaneously through the gastrointestinal tract without causing injury. However, some can cause serious complications which might require surgical intervention [4]. In our study, Abdominal pain, vomiting and paroxysmal crying were the common symptoms in the rst group which similar to other pediatric digestive diseases like appendicitis, intussusception and mesenteric lymphadenitis.…”
Section: Discussionsupporting
confidence: 68%
“…Jujubes, harvest in fall, are major agricultural crops in Xinjiang, mainland of China [3].Jujube pits, spindle-shaped objects with sharp ends, hard to pass through intestinal tract during peristalsis and discharge with feces when impaction happens. Unlike adults, children are not able to distinguish edible objects from non-edible objects and have poor swallowing coordination [4]. As a fruit often eaten in daily life, most of the parents underestimate the hazards of jujube pits.…”
Section: Introductionmentioning
confidence: 99%
“…9,17 However, several studies have suggested that social, economic, and cultural environments in which the child lives impact the prevalently ingested FB type. 2,9,10,[14][15][16][17] For instance, the most frequently ingested FBs in Western countries are coins, whereas fish bones are the most prevalent FBs in Asian countries, probably because of the higher consumption of fish without prior removal of bones. In a retrospective study in Iran, 7 coin ingestion accounted for only 16% of all cases, which was attributed to the less common use of coins as currency because of financial policies.…”
Section: Discussionmentioning
confidence: 99%
“…Along with pneumoperitoneum these injuries also causes peritonitis due to leakage of intestinal contents and this sign can be very easily elicited during clinical examination. Shao F et al in 2020 in his study observed that out of 35 children who ingested foreign body, 26 of them developed intestinal perforation and 9 of them presented with intestinal obstruction [7] . They also concluded that early identification of such cases can help in prevention of developing complication also early surgical intervention and removal of foreign body results in better outcome.…”
Section: Discussionmentioning
confidence: 97%